Changes in cortisol and immunoglobulin a concentrations in referees during a professional football match - Kokaly, M.; Peñailillo, L.; Villagrán, C.; Mackay, K.; Jannas, S.; Deldicque, L.; Zbinden-Foncea, H. (Journal of Sports Science & Medicine, 2018)
Football is an intermittent sport for players and referees, as both run at different intensities during a match to closely follow the actions on the pitch (Krustrup et al., 2009). Previous studies have reported that football referees run distances between 11 and 12 km per match, of which at least 10% is ran at high intensity (>18 km/h), reaching repeatedly 85 to 95% of their maximum heart rate (Weston et al., 2012), suggesting that a football match is a pronounced physiological stressor for referees. Moreover, referees are subjected to mental stress due to complex decision-making by dealing with players, coaches and audiences. Therefore, it seems clear that referees go through substantial physical and psychological stress during football matches that may be similar to the one experienced by players.